Inhibited early immunologic response is associated with hypertrophic scarring. Issue 10 (3rd August 2016) - Butzelaar, Liselotte; Schooneman, Dennis P. M.; Soykan, Ezgi A.; Talhout, Wendy; Ulrich, Magda M. W.; van den Broek, Lenie J.; Gibbs, Susan; Beelen, Robert H. J.; Mink van der Molen, Aebele B.; Niessen, Frank B.
Abstract: This study aimed to examine changes in the inflammatory response in early hypertrophic compared to normal wound healing. The immune system is thought to be involved in hypertrophic scar formation. However, the exact mechanism and time of onset of the derailment remain unknown. In a prospective observational study, skin biopsies were taken directly postwounding and 3 hours later from patients who had elective cardiothoracic surgery. The skin biopsies were analysed for mRNA, proteins and cells involved in the early inflammatory phase of wound healing. The endpoint was scar outcome (hypertrophic (HTS) or normal (NTS)) at one year after surgery. There were significant differences between the NTS and HTS groups regarding the fold changes of mRNA expression of P‐selectin during surgery. Postoperative skin concentrations of inflammatory proteins IL‐6, IL‐8 and CCL2 were significantly lower in the HTS compared to the NTS group. Also, a trend of higher pre‐operative M2 macrophage numbers was observed in the HTS group. Neutrophil numbers increased equally during surgery in both groups. The increase of P‐selectin mRNA in hypertrophic wound healing could affect leucocyte migration. The decreased concentrations of inflammatory proteins in hypertrophic wound healing indicate a reduced inflammatory response, which has consequences for the treatment of hypertrophic scarring during the early inflammatory phase. In a conclusion, alterations of wound healing associated with hypertrophic scarring are visible as early as 3 hours postwounding and include a reduced rather than increased inflammatory protein response.